The Relationship Between Family Resilience and Efforts to Prevent Acute Respiratory Infection (ARI) Among Children in Wetlands - Aminatul Fitri; Sri Wahyuni; Anisa Yulvi Azni; Nur Aulia (Indonesian Journal of Global Health Research, 2026)
Children living in wetlands are particularly susceptible to Acute Respiratory Infections (ARI), and family resilience plays a vital role in safeguarding their health. This study explored the association between family resilience and families’ efforts to prevent ARI in children aged 1–5 years. A quantitative descriptive correlational design was applied, involving 100 families in wetlands. Data were collected using the Family Resilience Assessment Scale (FRAS) and a validated ARI prevention questionnaire, both of which had been tested for validity and reliability. Data were analyzed using the Chi-square test. The findings revealed a significant relationship between family resilience and ARI prevention efforts (p = 0.012). Families with greater resilience were more consistent in maintaining hygiene, keeping their homes clean, and seeking timely medical care when respiratory symptoms appeared.